Combating money laundering in the age of digital transformation: A comparative study between Türkiye and Nigeria - Mouhamed Bachir DIOP (Journal of Economic Criminology)
The significance of digitalization due to technological advancements in the modern age is becoming increasingly apparent. However, as a result of the rapid global change, serious concerns arise regarding various aspects of proper digitalization, particularly how to leverage it while avoiding its potentially harmful effects. The numerous gaps that could be exploited create a more dangerous posture, especially concerning financial crimes. This study aims to illuminate a part of the legislative experiences of Türkiye and Nigeria in combating money laundering. The study examines each country's relevant approaches separately, comparing the mechanisms employed in the thick of the digital transformation era.